Korelasi antara Dosis Eksposur Timbal dengan Kadar Ureum dan Kreatinin Serum pada Wistar (Rattus norvegicus) - Atmawati, Baiq Jatna; Syamsun, Arfi (Faculty of Medicine Universitas Mataram, 2012)
Introduction: Clean air is hard to find these days, especially in big cities where industries and motor vehicles contribute to air pollution. It is almost about 85% of air pollution is caused by the emission of motor vehicles. One of the contaminants which are produced is lead. The lead which accumulates inside the tissues of the body will cause disorder mainly to the urinarius system (kidneys), liver, hematopoetic system, cardiovascular, and reproduction system. The objective of this research is to find out the correlation between the dosage of lead exposure with the level of serum ureum and creatinine on wistar rats (Rattus norvegicus). Method: This research applies a simple experimental research design which is called the post-test only control group design. This research participates with 6 research groups, that is, 4 for the treatment groups and 2 for the control groups. On the treatment groups, firstly, wistar rats are treated in a way which they are given a gradable dosageof acetic leads per orally. The level of acetic leads given in Treatment 1 (P1) is 1.1 ml, Treatment 2 (P2) is 0.825 ml, Treatment 3 (P3) is 0.55 ml, and Treatment 4 (P4) is 0.25 ml. After 24 hours (of acute exposure), the rats are anethesized by diethyl ether and then continue take the blood through the intracardiac. On control, on the other hand, no treatment at all is given to the rats. On Control 1, previously, the rats are anethesized with diethyl ether. On Control 2, however, they are not anesthesized but do decapytation. Result: Researchers have found the result that there is no significant correlation between the dosage of lead exposure towards the level of serum ureum and creatinine on wistar rats from the experiment of Control 1 and Control 2 (p>0.05). Researchers have found that the more reduced the dosage of the acetic lead, the more increasing the average of serum ureum. As for the creatinine, researchers have seen that there is no significant difference in the value between the treatment group and control group. Researchers have also found that there is no significant difference between the level of serum ureum and the level of creatinine on control group 1 and control group 2 (p>0.05). On the other hand, it is seen that there is difference on the value of ureum and creatinine in control 1 and in control 2. Conclusion: After conducting the experiment, researchers have found the result that there is no significant correlation between the dosage of lead exposure towards the level of serum ureum and creatinine on wistar rats from the experiment of Group 1 and Group 2 (p>0.05). On the other hand, it is seen that there is difference on the value of ureum and the value of creatinine in control group 1 (anesthesized with ether) and in control group 2 (without ether).